Comparación de la respuesta biológica en post larva litopenaeus vannamei obtenida en laboratorio con sistemas de producción orgánico y convencional - Novillo Navarro, Manuel Joel (2013)
Thecomparison studyofthe biological response oftheperformedlarvatwolaboratories, organicproduction(Treatment 1) and the secondconventional production(treatment 2) located in the province ofSalinas, MarBravo, eachI offerfour tankslaboratoryfor the studyand duringtwo production cycles. Following the protocolofeach laboratorywithoutchanging anythingstartedmakingparameters(oxygen, ammonia, temperature), from the time ofplantingin each laboratorytwice a day(morningand afternoon)while workmeasurementCunadoled him tomakethe larvawas ina stage ofPl-5 every day untilharvest,taking a sample of100shrimpfor measurementwhile thepl/ gramrealizeitwhen the larvawas ina stage ofpl-8 in the same wayuntilharvest. Forstatistical analysisofthe sizesandpl /gram dailywas requiredfortwo halfhypotheseswithindependentevidence(distribution oft)usinga software calledQEDStatistics1.0, resulting in no significant differencebetween the twotreatment, reaching obtain a bettersurvivalin treatment 1with an averageof 85%in comparison with thereflectiontreatment268.6% survival. With the developmentof this thesisis expectedto demonstratein the productiveand financiallarviculturawhat would bethe best investmentwhenyou decideto produceit.